The Influence of Product Quality, Price, and Service Quality on Consumer Purchase Decisions at Sahabat Tani Store, Sintang - Elvatriana Mulyawan; Neni Triana M (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to identify the effect of Product Quality, Price, and Service Quality on consumer Purchase Decisions at Sahabat Tani store in Sintang. This study uses an associative method. The population in this study consists of consumers who have purchased products at Sahabat Tani Store, with a sample of 150 respondents determined using a purposive sampling technique. Instrument testing techniques in this study include validity tests and reliability tests. Furthermore, the classical assumption tests used consist of normality tests, linearity tests, and multicollinearity tests. Hypothesis testing was conducted using multiple linear regression analysis, correlation coefficient, coefficient of determination, simultaneous test (F test), and partial test (t test). Based on the results of multiple linear regression analysis, the regression equation obtained is Y= 1.227+0.167X₁+0.303X₂+0.259X3. The correlation coefficient results show a value of 0.782, which means there is a strong relationship between Product Quality, Price, and Service Quality on Purchase Decisions. The coefficient of determination shows a value of 0.611, which means that Purchase Decisions are influenced by Product Quality, Price, and Service Quality by 61.1%, while the remaining 38.9% is influenced by other variables not examined in this study. The simultaneous test results show that Product Quality, Price, and Service Quality together have a positive and significant effect on Purchase Decisions. And based on the partial test results, it is known that Product Quality, Price, and Service Quality have a positive and significant effect on Purchase Decisions.